Elliptic virtual structure constants and generalizations of BCOV-Zinger formula to projective Fano hypersurfaces - Masao Jinzenji; Ken Kuwata (Journal of High Energy Physics)
Abstract In this paper, we propose a method for computing genus 1 Gromov-Witten invariants of Calabi-Yau and Fano projective hypersurfaces using the B-model. Our formalism is applicable to both Calabi-Yau and Fano cases. In the Calabi-Yau case, significant cancellation of terms within our formalism occurs, resulting in an alternative representation of the BCOV-Zinger formula for projective Calabi-Yau hypersurfaces.